How Fair is Workfare? Gender, Public Works, and Employment in Rural Ethiopia - Quisumbing, Agnes R.; Yohannes, Yisehac (World Bank, 2005)
The authors use the Ethiopian Rural Household Survey to examine the gender dimensions of public works. They use three rounds of a panel conducted in 1994-95 to explore the determinants of participation in, days worked, wages, and earnings from wage labor, food-for-work (FFW), and self-employment. Then they analyze public works data collected in 1997, together with program data collected in 2003. FFW operates in a similar fashion with other labor markets in Ethiopia where female participation is low. Gender differences are important in the participation decision, but operate differently in different types of labor markets. Better-educated women are more likely to participate in the wage labor market, while higher livestock holdings diminish participation more for women. Females with more schooling are also more likely to participate in FFW. Men s and women s participation in FFW and self-employment responds differently to household and community shocks. After controlling for selection in which gender plays an important role, gender disadvantages in the wage labor market and FFW are insignificant. Returns to schooling and height are consistently positive in both wage labor and FFW, suggesting returns to human capital investment, even in the low-skill labor markets of rural Ethiopia. Program characteristics significantly affect participation, with differential effects on men and women. Participation, days worked, wages, and earnings vary according to the type of project. Relative to infrastructure projects, water, social services, and other projects decrease participation probabilities. Distance has a strong negative effect on women s participation relative to men s.